MRI-informed muscle biopsies correlate MRI with pathology and DUX4 target gene expression in FSHD. (12th October 2018) - Wang, Leo H; Friedman, Seth D; Shaw, Dennis; Snider, Lauren; Wong, Chao-Jen; Budech, Chris B; Poliachik, Sandra L; Gove, Nancy E; Lewis, Leann M; Campbell, Amy E; Lemmers, Richard J F L; Maarel, Silvère M; et al.
Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a common, dominantly inherited disease caused by the epigenetic de-repression of the DUX4 gene, a transcription factor normally repressed in skeletal muscle. As targeted therapies are now possible in FSHD, a better understanding of the relationship between DUX4 activity, muscle pathology and muscle magnetic resonance imaging (MRI) changes is crucial both to understand disease mechanisms and for the design of future clinical trials. Here, we performed MRIs of the lower extremities in 36 individuals with FSHD, followed by needle muscle biopsies in safely accessible muscles. We examined the correlation between MRI characteristics, muscle pathology and expression of DUX4 target genes. Results show that the presence of elevated MRI short tau inversion recovery signal has substantial predictive value in identifying muscles with active disease as determined by histopathology and DUX4 target gene expression. In addition, DUX4 target gene expression was detected only in FSHD-affected muscles and not in control muscles. These results support the use of MRI to identify FSHD muscles most likely to have active disease and higher levels of DUX4 target gene expression and might be useful in early phase therapeutic trials to demonstrate target engagement in therapies aiming to suppress DUX4 expression.